Principal instructional leadership and teacher readiness for change to implement school based assessment in secondary schools - Abdul Aziz, Nor Azni; Asimiran, Soaib; Foo, Say Fooi; Hassan, Aminuddin (Human Resource Management Academic Research Society, 2018)
The instructional leadership of a principal has a positive effect on teacher readiness for change. As such, the purpose of this study was to examine the relationship between three dimensions of principal instructional leadership and teacher readiness for change in implementing School-Based Assessment (SBA) among secondary school teachers in Selangor, Malaysia. A quantitative correlational design was used to collect the data using an adapted questionnaire to measure principal instructional leadership and teacher readiness for change. Data was obtained from 402 secondary teachers in Selangor, who were selected through stratified random sampling. Data was analysed using SPSS in the form of mean, standard deviation, and Pearson correlation analysis. The findings show that the level of instructional leadership of the principal as a whole is high with a mean of 3.68 and standard deviation 0.57. The overall level of readiness for change among the teachers is high with a mean of 3.72 and standard deviation of 0.51. Tests to determine the correlation between the dimensions of the mission of school (r = 0.321, p <0.05) and creating school learning climate (r = 0.371, p <0.05) with readiness for change among the teachers show a significant positive but low correlation. Meanwhile, the relationship between managing the teaching program (r = 0.470, p <0.05) with readiness for change among the teachers shows a significant positive but moderate correlation. Overall, the effect of principal instructional leadership on readiness for change shows that instructional leadership has a positive and significant correlation with the readiness for change. This study provides the basis for teacher readiness to face changes and strengthening the educational administration field in enhancing instructional leadership in schools.